SISTEM INFORMASI TATA LETAK ARSIP DI KANTOR PELAYANAN PAJAK PRATAMA LANGSA - Muhammad Nazir Syafwan; Liza Fitria (E-Jurnal Universitas Samudra, 2020)
Archives are one source of information that has an important function to support the administrative and management activities of an agency. All activities carried out by the agency, whether in the form of proposals, correspondence or other documents, will become archives. Considering the increasing number of archives created and accepted by KPP Pratama Langsa, a good archive arrangement is needed, known as the archiving system. The purpose of the archive layout information system at the Langsa Pratama Tax Service Office is to record the layout of files that have been archived through the system. In the archive layout information system, it is used to organize the layout of the archives in the KPP Pratama Langsa office and to record the records that are entered into the system.